UMP, SME Corporation Malaysia collaborate with TUBE IPT Programme to produce entrepreneurial graduates - Mimi Rabita, Abdul Wahit (2021)
PUTRAJAYA, 30 September 2021 - Entrepreneurship would be one of the career options for graduates when the collaboration between Universiti Malaysia Pahang (UMP) and SME Corporation Malaysia (SME Corp) was signed through the implementation of the Tunas Usahawan Belia Bumiputera (TUBE@IPT) programme 8.0 launched recently.